Evolution of COVID-19 seroprevalence in blood banks during the pandemic in the Lima region, Peru - Fuentes Rivera, Teófilo José (2024)
Introduction. Peru was one of the countries most affected by the COVID-19 pandemic, with more than 220,000 deaths recorded due to SARS-CoV-2 infection. Given the constant mutations of the virus and registered variants, it is important to carry out research that reflects the evolution of the humoral immune state. Objective. Measure the seroprevalence of COVID-19 during the pandemic in the department of Lima in the period between April 1, 2020 and June 30, 2022, in donor samples from 6 hospital blood banks public of Lima, Peru. Methods. A descriptive, transversal, observational and retrospective study was carried out evaluating the presence of IgM/IgG antibodies against SARS-CoV-2 using lateral flow chromatographic immunoassay in samples from healthy and asymptomatic donors from blood banks of 6 health facilities in the department of Lima. Results. A progressive increase in the seroprevalence of IgG and total reactivity of IgM/ IgG antibodies against SARS-CoV-2 will be observed as follows: 22,6% - 32,7% during 2020; 53,9% - 58,1% during 2021; 88,9% - 93,3% during the first half of 2022. Conclusions. The reactivity and presence of anti- SARS-CoV-2 antibodies progressively increase during the COVID-19 pandemic from 11,2% to 98,4% in the samples evaluated, possibly with the impact of the pandemic waves and the active vaccination campaign against COVID-19.